Dinâmica Hamiltoniana simplética: capacidade de Hofer-Zehnder - Ferreira, Brayan Cuzzuol (2019)
This dissertation presents some fundamental theorems on Symplectic Geometry including Darboux’s theorem and Gromov’s nonsqueezing theorem. Furthermore, we study the existence of periodic orbits of hamiltonians systems. The Hofer-Zehnder capacity was the main tool used to obtain the results.Hofer-Zehnder capacity was the main tool used to obtain the results